2004
DOI: 10.4314/sajas.v34i1.3806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein supplementation and urea treatment on utilization of maize stover by Red Maasai sheep

Abstract: Six Red Maasai sheep were used to investigate the effects of urea treatment and cotton seed cake supplementation of maize stover on intake, digestibility and rumen fermentation parameters. The basal feeds were Rhodes grass (Chloris gayana) hay (H), untreated maize (Zea mays) stover (US) and treated maize stover (TS), each of which was supplemented with 100 g of cotton seed cake (CSC) to make H+CSC, US+CSC and TS+CSC. These were offered over four feeding periods in a completely randomized block design, with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
3
6
1
1
Order By: Relevance
“…In this work, untreated maize straw had an in vitro DM digestibility of 603.5 (SEM±14.4) g/kg, whilst the urea treated maize straw had an in vitro DM digestibility of 710.0 (SEM±1.53) g/kg representing a 17.7% increase in digestibility. Woyengo et al (2004) report a 46% increase in maize straw digestibility, although the digestibility of their untreated maize straw was significantly lower than the initial digestibility of untreated straw herein reported. Oji et al (2007), using maize straw with a better initial digestibility, report 15.3% higher digestibility when treated with urea; and Ramírez et al (2007) report an improvement on the DM digestibility of urea treated maize straw of 14.6% over the untreated control.…”
Section: In Vitro Digestibility Of Maize Strawcontrasting
confidence: 63%
See 1 more Smart Citation
“…In this work, untreated maize straw had an in vitro DM digestibility of 603.5 (SEM±14.4) g/kg, whilst the urea treated maize straw had an in vitro DM digestibility of 710.0 (SEM±1.53) g/kg representing a 17.7% increase in digestibility. Woyengo et al (2004) report a 46% increase in maize straw digestibility, although the digestibility of their untreated maize straw was significantly lower than the initial digestibility of untreated straw herein reported. Oji et al (2007), using maize straw with a better initial digestibility, report 15.3% higher digestibility when treated with urea; and Ramírez et al (2007) report an improvement on the DM digestibility of urea treated maize straw of 14.6% over the untreated control.…”
Section: In Vitro Digestibility Of Maize Strawcontrasting
confidence: 63%
“…The treatment with ammonia or urea has the added advantage of a better Nitrogen supply, which enhances ruminal digestion (Woyengo et al 2004;Oji et al 2007;Ramírez et al 2007). In this work, untreated maize straw had an in vitro DM digestibility of 603.5 (SEM±14.4) g/kg, whilst the urea treated maize straw had an in vitro DM digestibility of 710.0 (SEM±1.53) g/kg representing a 17.7% increase in digestibility.…”
Section: In Vitro Digestibility Of Maize Strawmentioning
confidence: 99%
“…This might be related to when protein degradation exceeds the rate of carbohydrate fermentation, large amounts of nitrogen compounds can be excreted via urine and feces. [22] The lambs' performance was improved by the addition of SMB to their diets. These results agree with those reached by other researchers [20,23] who reported that the ADG and the BW gain of different sheep breeds that consumed higher levels of protein supplements were enhanced by protein supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Kombinasi tersebut mampu meningkatkan kadar protein kasar menjadi 11% dan menurunkan kadar silika menjadi 11,97%. Sedangkan penelitian Woyengo et al (2004) pada domba Red Maasai dengan fistula rumen menunjukkan bahwa penambahan urea dan bungkil biji kapas pada limbah tanaman jagung mampu meningkatkan kadar protein kasar dan menurunkan kandungan NDF. Lebih lanjut, penelitian tersebut juga menunjukkan bahwa kecernaan bahan kering, bahan organik, dan kadar protein kasar mengalami peningkatan.…”
Section: Peran Urea Dalam Pening-katan Nilai Nutrisiunclassified